Does Managerial Compensation Drive Tax Avoidance? The Role of Financial Distress and Accounting Conservatism - Sabar Pardamean Lumbantobing; Etty Murwaningsari; Mohd Faizal Basri (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2026)
Corporate tax minimisation has become a critical global concern, particularly in developing economies where tax revenue remains below optimal levels. Prior studies examining the effects of executive remuneration and financial distress on tax avoidance report inconsistent findings, indicating the need for a contingent explanatory factor. This study investigates the influence of management compensation and financial distress on corporate tax avoidance, measured using the cash effective tax rate (CETR), while assessing the moderating role of accounting conservatism. Using a quantitative explanatory design, this research analyses 612 firm year observations from 124 non financial companies listed on the Indonesian capital market during 2019 2023. Panel data regression with fixed effects is applied, with model selection based on Chow, Hausman, and Breusch Pagan Lagrange Multiplier tests, and moderation captured through interaction terms. The results indicate that management compensation and financial distress significantly increase tax avoidance, reflected in lower CETR values. However, accounting conservatism weakens these relationships, suggesting its role in limiting opportunistic managerial behaviour under both incentive driven and pressure driven conditions. This finding clarifies prior mixed evidence by demonstrating that the compensation tax avoidance and distress tax avoidance relationships are conditional on firms’ reporting practices. The study contributes to the literature by showing that accounting conservatism functions both as a direct determinant and as a moderating mechanism in corporate tax behaviour. Practically, the findings highlight the importance of designing balanced compensation schemes and promoting conservative reporting standards to reduce aggressive tax practices, particularly in firms facing high financial pressure.